2020
DOI: 10.21203/rs.3.rs-31142/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prognostic Impact of Coagulopathy in Patients with COVID-19: a Meta-analysis of 35 Studies and 6427 Patients

Abstract: Coronavirus Disease 2019 (COVID-19) is a highly contagious disease that appeared in China in December 2019. Several patients with severe COVID-19 infection can develop a coagulopathy according to the ISTH-criteria for disseminated intravascular coagulopathy (DIC). We conducted a meta-analysis of all available studies on COVID-19 to explore the impact of coagulopathy on severe illness and mortality. An electronic search was performed within PubMed, Google Scholar and Scopus electronic databases. The primary end… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…It has been reported that patients with non-severe disease have a lower level of D-Dimer as compared to those with severe disease. 24 Our sample was a homogenous one including only cases with severe disease admitted to intensive care unit. To the best of our knowledge, this is the rst study from South Asia on the role of biomarkers in severe COVID-19.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that patients with non-severe disease have a lower level of D-Dimer as compared to those with severe disease. 24 Our sample was a homogenous one including only cases with severe disease admitted to intensive care unit. To the best of our knowledge, this is the rst study from South Asia on the role of biomarkers in severe COVID-19.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that patients with non-severe disease have a lower level of D-Dimer as compared to those with severe disease. 24 Our sample was a homogenous one including only cases with severe disease admitted to intensive care unit. To the best of our knowledge, this is the first study on the role of biomarkers in COVID-19 patients admitted to intensive care unit.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with COVID-19 infection have worse prognosis if they develop coagulopathy during the course of the disease (40) . Older age, the presence of certain comorbidities or underlying conditions, and some image findings related to coagulation abnormalities are also associated with mortality in COVID-19 infection (41) .…”
Section: Stratification Of Coagulation State In Patientsmentioning
confidence: 99%